Perceptions of nurse educators and nursing students on the model for facilitating 'presence' in large class settings through reflective practices: a contextual inquiry - Kathleen Froneman; Emmerentia du Plessis; Anna Catharina van Graan (BMC, 2023)
Abstract Background Nursing education starts in the classroom environment with a focus on the nurse educator-nursing student relationship. 'Presence' is defined as "a practice where the caregiver relates her/himself to the other in an attentive and dedicated way, by doing so learns to see what is at stake for the other; from desires to fear, and, in connection with this, come to understand what could be done in this particular situation and who she/he can be for the other". 'Presence' forms an integral part of the nursing profession and the value thereof should be facilitated during teaching and learning. Reflective practices may offer a teaching-learning strategy to facilitate presence in nursing students by nurse educators in large class settings. Having large classes presents challenges including from nurse educators' lack of knowledge about alternative teaching approaches; time demands for designing, implementing and testing new teaching methods; a lack of confidence in implementing new teaching approaches in the classroom; selecting and grading assessments; as well as feelings of discomfort and anxiety. A model to facilitate presence through reflective practices has already been developed and published by the present authors. The model relies on well-established steps in theory development covering concept analysis, model development and description (published in two papers by the present researchers) and model evaluation (the subject of this paper). The evaluation was carried out by a panel of experts and nursing participants. Methods An explorative and descriptive qualitative design was followed. The developed model was evaluated and refined in two steps (covered in this paper). In Step 1, the model was evaluated by a panel of experts in model development, reflective practices and presence. The panel used critical reflection resulting in the refinement of the model. Step 2 involved an empirical phase where the model was evaluated by participants through participatory evaluation. Participants were selected through purposive sampling. Data collection methods included online semi-structured focus group interviews with nurse educators and virtual World Café sessions with nursing students. Content analysis was done through open coding. Results Five themes emerged from the empirical phase, namely: Theme 1: understanding of the model; Theme 2: benefits of the model; Theme 3: limitations of the model; Theme 4: pre-existing conditions needed for successful implementation of the model; and Theme 5: recommendations for further development of the model. Conclusions The results produced a refined model to be implemented into the curriculums of undergraduate, postgraduate and continuous professional development programmes across nursing education institutions. This model will significantly contribute to the body of knowledge and increase nurses' awareness of presence by transforming the way they feel, think, care and act in practice, which contributes to personal and professional development.